Study of the structural curvature in Mo2C derived carbons with contrast matched small-angle neutron scattering. (January 2021) - Palm, Rasmus; Härmas, Riinu; Härk, Eneli; Kent, Ben; Kurig, Heisi; Koppel, Miriam; Russina, Margarita; Tallo, Indrek; Romann, Tavo; Mata, Jitendra; Tuul, Kenneth; Lust, Enn
Abstract: The influence of the synthesis conditions on the formation of the porous and the graphitic structure of carbon materials was investigated on Mo2 C-derived carbon materials synthesized at different temperatures ( T syn from 700 to 1000 °C). Contrast matched small-angle neutron scattering method was used to obtain explicit information about the pore and pore wall structure of the carbons. It was found that carbons formed at lower T syn exhibit prevalently nano-scale cylindrical geometry and an increase in T syn promotes the formation of slit-like structures. Additionally, partial contrast matching was used, which effectively made the pore walls wider, enabled to „hide" the smaller pores, exposing in greater detail the geometries of larger mesopores. The geometry of larger structures (e.g. pores and pore walls) changes from mixed cylindrical and slit-like to completely slit-like with the increase of T syn . The observed change of the geometries, expressed by the increase in the dimensionality parameter, that increases from 1.2 to 1.8, empirically correlates with the decrease in the disorder between graphitic layers. Thus, we conclude that the cylindrical structures are caused by the curvature in graphitic layers formed at lower T syn (≤800 °C). Graphical abstract: Image 1